Ceftolozane/tazobactam for the treatment of complicated urinary tract and intra-abdominal infections. (February 2015) - Bassetti, Matteo; Righi, Elda
ABSTRACT : High rates of morbidity and mortality have been linked to the emergence of antimicrobial-resistant Gram-negative pathogens, especially in the hospital setting. Infections due to extended-spectrum-β-lactamase producing Enterobacteriaceae (e.g., Escherichia coli, Klebsiella pneumoniae ) and multidrug-resistant Pseudomonas aeruginosa pose a major health threat and dramatically reduce the therapeutic options to achieve an appropriate treatment. There is a need for novel antimicrobials that could provide clinical efficacy toward multidrug-resistant Gram-negative pathogens, including extended-spectrum-β-lactamase and carbapenemase producers. Ceftolozane/tazobactam is a novel antipseudomonal cephalosporin associated with a well-established β-lactamase inhibitor currently in clinical development for the treatment of complicated intra-abdominal infections, complicated urinary tract infections and nosocomial pneumonia. Phase II and III trials have shown high efficacy and good tolerability in complicated urinary and intra-abdominal infections compared with standard therapy. A study for the treatment of nosocomial pneumonia is planned.